Amalan kepimpinan instruksional pengetua sekolah menengah berprestasi tinggi dengan sekolah menengah berprestasi rendah di daerah Kota Setar Kedah Darul Aman - Mohd Zaini, Ismail (2009)
The purpose of this study was to identify the difference between the instructional leadership as practised by school principals in high and low performing secondary schools in Kota Setar district. The research samples were consist of 296 teachers of both categorized schools involved in the study. The instrument used to measure the instructional leadership in this research was the Principal Instructional Management Rating Scale (PIMRS) which was established by Hallinger dan Murphy (1987). The instruments were gathered, checked and analyzed with descriptive of percentage, mean, frequency and t-test analyses, through the Statistical Package for The Social Science (SPSS) version 15. Result indicated that there is a difference between the instructional leadership practised by the school principals in high and low performing secondary schools.